If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2h + -12 = 2 Reorder the terms: -12 + 2h = 2 Solving -12 + 2h = 2 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2h = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 2h = 2 + 12 2h = 2 + 12 Combine like terms: 2 + 12 = 14 2h = 14 Divide each side by '2'. h = 7 Simplifying h = 7
| -7x-24=312 | | 2x+40x= | | 4x-15(6-x)=-8(5-3x) | | -20p-5=-765 | | 77=5y-13 | | 16=4s-4 | | 9x+4.86=3x+12 | | 10x^2-50x-60=0 | | 7x-13=4x-4 | | 7a=10 | | 4y+70=6 | | 4u-10=24 | | 4x-15(6-x)=8(5-3x) | | 3r-7s=K | | 6/x=24/(30-2x) | | 13y+3=-335 | | 2x-8+6-x=16 | | y+4=-2(x+6) | | (x-5)=x-11 | | (50.75+21.59)= | | 17m-8=12m+7 | | -3p=3p+36 | | 19=4w+7 | | x=7+3i | | x^9=36 | | 10x+16=4x+118 | | 5x+20+6x=7x+40 | | 34=5y+15 | | 10u=u+54 | | -4c-8=192 | | 22y=308 | | sqrtx-5=x-11 |